First principles calculation of lithium-phosphorus co-doped diamond - Shao, Q.Y.; Wang, G.W.; Zhang, J.; Zhu, K.G. (Condensed Matter Physics, 2013)
We calculate the density of states (DOS) and the Mulliken population of the diamond and the co-doped diamonds with different concentrations of lithium (Li) and phosphorus (P) by the method of the density functional theory, and analyze the bonding situations of the Li-P co-doped diamond thin films and the impacts of the Li-P co-doping on the diamond conductivities. The results show that the Li-P atoms can promote the split of the diamond energy band near the Fermi level, and improve the electron conductivities of the Li-P co-doped diamond thin films, or even make the Li-P co-doped diamond from semiconductor to conductor. The affection of Li-P co-doping concentration on the orbital charge distributions, bond lengths and bond populations is analyzed. The Li atom may promote the split of the energy band near the Fermi level and also may favorably regulate the diamond lattice distortion and expansion caused by the P atom. Ми обчислюємо густину станiв (DOS) i заселення Муллiкена алмазу та спiвлегованих алмазiв з рiзними концентрацiями лiтiю (Li) i фосфору (P) за допомогою методу функцiоналу густини та аналiзуємо випадки зв’язування тонких плiвок Li–P спiвлегованого алмазу, а також впливи Li–P спiвлегування на провiднiсть алмазу. Результати показують, що атоми Li–P можуть активiзувати розщеплення енергетичної зони алмазу поблизу рiвня Фермi, а отже покращити провiднiсть електронiв тонких плiвок Li–P спiвлегованого алмазу, або ж навiть перетворити Li–P спiвлегований алмаз з напiвпровiдника у провiдник. Проаналiзовано вплив Li–P концентрацiї спiвлегування на орбiтальний розподiл заряду, довжину зв’язку та заселенiсть зв’язку. Атом Li може активiзувати розщеплення енергетичної зони поблизу рiвня Фермi, а також може благотворно регулювати спотворення та розширення кристалiчної гратки алмазу.